Video-Mosaicked Handheld Dual-Axis Confocal Microscopy of Gliomas: An ex vivo Feasibility Study in Humans - Fujita, Yoko; Wei, Linpeng; Cimino, Patrick J.; Liu, Jonathan T. C.; Sanai, Nader (Frontiers in Oncology, 2020)
Background Intraoperative confocal microscopy can enable high-resolution cross-sectional imaging of intact tissues as a noninvasive real-time alternative to gold-standard histology. However, all current means of intraoperative confocal microscopy are hindered by a limited field of view, presenting a challenge for evaluating gliomas, which are highly heterogeneous. Objective This study aimed to evaluate the benefit of image-mosaicking with handheld dual-axis confocal (DAC) microscopy of fresh human glioma specimens. Methods Fresh human glioma specimens from 6 patients were labeled with a fast-acting topical stain (acridine orange) and imaged using a newly developed DAC microscope prototype. Results Mosaicked images from a DAC microscope provide more accurate and representative views of gliomas, including the ability to visualize gradual transitions from areas of dense cellularity to sparse cellularity within the tumor. These mosaicked images correlated well with corresponding hematoxylin and eosin (H&E) histology. Conclusion LS-DAC microscopy provides high-resolution, high-contrast images of glioma tissues that agree with corresponding H&E histology. Compared with individual image frames, mosaicked images provide more accurate representations of the overall cytoarchitecture of heterogeneous glioma tissues. Further investigation is needed to evaluate the ability of high-resolution mosaicked microscopy to improve the extent of glioma resection and patient outcomes.